Proposed new design scheme for Miss Sixty retail shop at Lot 03- 61,62 63 & 64, Third Floor, Berjaya Times Square, No 1 Jalan Imbi, 55100, Kuala Lumpur / Wan Zurainor Wan Zainun - Wan Zainun, Wan Zurainor (2006)
The purposed of this final project is to realize the design process that involve in the preliminary findings, analysis case study and synthesizing Diploma of Interior Architecture. The suggested title of this project is Proposed New Design Scheme for MISS SIXTY Retail Shop at lot 03-61 , 62, 63 and 64, Third Floor, Berjaya Times Square, No 1 Jalan Imbi, 55100, Kuala Lumpur Before writing this documentation, a lot of procedures has to be met and must follow a systematic process. Various important factors must be considered especially inside the angular space including environment outside the building. The first step before I started this project is to identify constraints and limitations of the existing site, interior and exterior. This is extremely important because, it is aimed to explain what the site problem is and how it can be solve with the project. Research begins from basic design principles up to building roof. Besides that, the research of interior space must also be considered as a case study. The nature of the case study directly or indirectly related to the project that I have proposed. Research and data that I have collected are analysis, and lastly synthesized into my design.